A Pentecostal Reception History of the Book of Judges - Martin, Lee Roy (Old Testament Essays, 2023)
This early Pentecostal reception history aims to locate the book of Judges within the Pentecostal context and to discover the effects of the book on the tradition’s theology and practice. The study examines North American periodicals (plus Confidence, a British publication) from the beginning of 1906 (the start of the Azusa St. revival) to the end of 1925, a period that historian Walter J. Hollenweger describes as the “heart” of the Pentecostal movement. These early voices help to shape a Pentecostal approach to the book of Judges as they show how this segment of the first generation of Pentecostals struggled with issues such as paradigms of leadership, the necessity of Spirit empowerment, the role of women in ministry and the relationship between purity and power. The testimonies, sermons and articles reviewed here demonstrate that some early Pentecostals identified with the stories and characters in Judges and appropriated them to the Pentecostal context. https://doi.org/10.17159/2312-3621/2022/v35n3a8